The Island of Amsterdamøya: A key site for studying past climate in the Arctic Archipelago of Svalbard. (1st March 2018) - Bakke, Jostein; Balascio, Nicholas; van der Bilt, Willem G.M.; Bradley, Raymond; D' Andrea, William J.; Gjerde, Marthe; Ólafsdóttir, Sædís; Røthe, Torgeir; De Wet, Greg
Abstract: This paper introduces a series of articles assembled in a special issue that explore Holocene climate evolution, as recorded in lakes on the Island of Amsterdamøya on the westernmost fringe of the Arctic Svalbard archipelago. Due to its location near the interface of oceanic and atmospheric systems sourced from Arctic and Atlantic regions, Amsterdamøya is a key site for recording the terrestrial response to marine and atmospheric changes. We employed multi-proxy approaches on lake sediments, integrating physical, biogeochemical, and isotopic analyses to infer past changes in temperature, precipitation, and glacier activity. The results comprise a series of quantitative Holocene-length paleoclimate reconstructions that reveal different aspects of past climate change. Each of the four papers addresses various facets of the Holocene climate history of north-western Svalbard, including a reconstruction of the Annabreen glacier based on the sedimentology of the distal glacier-fed lake Gjøavatnet, a reconstruction of changing hydrologic conditions based on sedimentology and stratigraphy in Lake Hakluytvatnet, reconstruction of summer temperature based on alkenone paleothermometry from lakes Hakluytvatnet and Hajeren, and a hydrogen isotope-based hydrological reconstruction from lake Hakluytvatnet. We also present high-resolution paleomagnetic secular variation data from the same lake, which document important regional magnetic field variations and demonstrate the potential for use in synchronizing Holocene sedimentary records in the Arctic. The paleoclimate picture that emerges is one of early Holocene warmth from ca. 10.5 ka BP interrupted by transient cooling ca. 10-8ka BP, and followed by cooling that mostly manifested as two stepwise events ca. 7 and 4 ka BP. The past 4ka were characterized by dynamic glaciers and summer temperature fluctuations decoupled from the declining summer insolation. Highlights: We have reconstructed the glacier Annabreen based on the sedimentology of the distal glacier-fed lake Gjøavatnet. We have reconstructed hydrological conditions based on sedimentology and stratigraphy in Lake Hakluytvatnet together with hydrogen isotopes. We have reconstructed summer temperature based on alkenone paleothermometry from lakes Hakluytvatnet and Hajeren. The early Holocene was warm from ca. 10.5 ka BP interrupted by transient cooling between 10 to 8ka BP. The past 4ka were characterized by dynamic glaciers and summer temperature decoupled from the declining summer insolation.